Combination treatment for advanced hepatocellular carcinoma with portal vein tumour thrombus: A case report. Issue 2 (February 2021) - Wang, Jianrong; Wang, Junxue; Wang, Jianzhu; Qian, Ziliang; Xu, Wensheng; Hang, Xiaofeng
We present a case of a 43-year-old man with advanced hepatocellular carcinoma (HCC) with portal vein tumour thrombus. Initially, transcatheter arterial chemoembolization (TACE) was performed. Although alpha-fetoprotein (AFP) levels decreased, circulating tumour DNA (ctDNA) levels showed an upward trend, and abdominal magnetic resonance imaging (MRI) showed that tumours in the portal vein had increased. Based on ctDNA profiling, apatinib and anti-programmed cell death protein 1 (anti-PD-1) antibodies and were sequentially administered. Approximately three months later, intrahepatic tumours had significantly diminished and AFP and ctDNA levels had reduced. The response was sustained at the 23-month follow-up and the patient was in good health. Combination treatment of TACE, apatinib and anti-PD-1 antibodies was effective, and profiling of ctDNA fragmentation may be beneficial in the therapeutic management of patients with HCC.